Microstructure and dielectric properties of bismuth germanate glass-ceramics - Puripat Kantha (2018)
Bismuth germanate composites containing Bi 2 GeO 5 -Bi 4 Ge 3 O 12 phases were prepared by glass ceramic method and sintering techniques. The existences of three bismuth germanate crystals of Bi 2 GeO 5 , Bi 4 Ge 3 O 12 and BiBO 3 were found in XRD patterns. The amount of each phase depended mostly on the sintering temperature where the Bi 4 Ge 3 O 12 phase was found to increase with increasing sintering temperature. The mixing of round and pyramidal shape crystals was observed in the sample sintered at 650°C. This gave rise to the improvement in its dielectric properties where the ε r was found to increase from ∼78 to ∼395 for the sample sintered at 500°C and 650°C, respectively. Moreover, the tanδ was found to decrease greatly with increasing sintering temperature. Thus, this Bi 2 GeO 5 -Bi 4 Ge 3 O 12 composite may be considered as a promising candidate of microwave dielectric materials. Copyright © Taylor & Francis Group, LLC.